Availability Of Essential Drugs for Managing HIV-Related Pain and Symptoms Within 120 PEPFAR-Funded Health Facilities in East Africa: A Cross-Sectional Survey With Onsite Verification - Harding, Richard; Simms, Victoria; Penfold, Suzanne; Mwangi-Powell, Faith; Namisango, Eve; Moreland, Scott; Atieno, Mackuline; Kataike, Jennifer; Nsubuga, Clare; Munene, Grace; Banga, Geoffrey; Higginson, Irene J. (Palliative medicine, 2014)
World Health Organization’s essential drugs list can control the highly prevalent HIV-related pain and symptoms. Availability of essential medicines directly influences clinicians’ ability to effectively manage distressing manifestations of HIV.To determine the availability of pain and symptom controlling drugs in East Africa within President’s Emergency Plan for AIDS Relief–funded HIV health care facilities.Directly observed quantitative health facilities’ pharmacy stock review. We measured availability, expiration and stock-outs of specified drugs required for routine HIV management, including the World Health Organization pain ladder.A stratified random sample in 120 President’s Emergency Plan for AIDS Relief–funded HIV care facilities (referral and district hospitals, health posts/centres and home-based care providers) in Kenya and Uganda.Non-opioid analgesics (73%) and co-trimoxazole (64%) were the most commonly available drugs and morphine (7%) the least. Drug availability was higher in hospitals and lower in health centres, health posts and home-based care facilities. Facilities generally did not use minimum stock levels, and stock-outs were frequently reported. The most common drugs had each been out of stock in the past 6 months in 47% of facilities stocking them. When a minimum stock level was defined, probability of a stock-out in the previous 6 months was 32.6%, compared to 45.5% when there was no defined minimum stock level (χ2 = 5.07, p = 0.024).The data demonstrate poor essential drug availability, particularly analgesia, limited by facility type. The lack of strong opioids, isoniazid and paediatric formulations is concerning. Inadequate drug availability prevents implementation of simple clinical pain and symptom control protocols, causing unnecessary distress. Research is needed to identify supply chain mechanisms that lead to these problems.
Keywords: HIV, pharmacy, East Africa, health care surveys, pain, symptoms, drug availability